Mexico's "catch-22": The implications of being a trade and climate partner of the United States and the European Union - Simone Lucatello (German Institute of Development and Sustainability (IDOS), 2022)
Under the current global environmental governance and trade regimes, several initiatives, such as the new United States-Mexico-Canada Agreement, the European Union's European Green Deal, and regional free trade agreements the European Union has implemented with strategic partners like Mexico, are prompting a vibrant discussion on how trade agreements can be used as a potential mechanism to create enforceable cross-border commitments to tackle climate change. However, to cut greenhouse gas emissions within a few decades, a decisive departure from current trends in emission and trade policies is required by all countries, both developed and developing. As a result, politicians, scholars and experts around the world have looked to trade agreements as a possible tool for reaching global climate commitments, either related to or independent from the Paris Agreement. But how well do these agreements suit this purpose? Carbon-intensive products worldwide increased when tariff reductions were implemented, resulting in destructive practices for many countries, particularly those in the Global South. For countries such as Mexico, the nexus between trade and climate change is not easy to address: the country is trapped between its ambitions to play a role in global trade platforms as an industrial manufacturer and agricultural exporter and its desire to be recognized as a global actor in climate change policy and actions within the global community. Despite recent changes in climate and environmental politics under the administration of President Andrés Manuel López Obrador (2018-2024), Mexico is a middle-income country with a long-standing tradition as climate champion and environmental leader in the Global South and needs to make clear where it stands under the new global environmental and ecological transition scenario imposed by the climate crisis and trade-related issues. The "entanglement" of global trade treaties and commitments under the current climate crisis, represents a major shift for Mexico. Caught between the new US-Mexico-Canada Agreement, the EU-Mexico Trade Agreement and the possible impacts of the European Green Deal, Mexico needs to define its role in trade and environmental terms alongside giant partners such as the United States and the European Union, while defending its role as a regional power. If the European Green Deal takes off as an international driver for deepening climate and sustainable development goals with European Union strategic partners, it remains to be seen how Mexico will respond to the challenge. In this paper we address the possible implications for Mexico under each of these instruments. We look at the interplay between them, explore the linkages and possible conflictual pathways, and "disentangle" the schemes in which trade and climate change are interconnected. Mexico may be trapped in a "catch-22" situation. Environmental provisions embedded in trade treaties provide critical benefits to the country, but this often comes at the expense of "unacceptable" environmental enforcement measures that can put at risk national development plans, especially at a time when the environment and climate change issues are not at the top of the current administration's political agenda.
Keywords: 330; European Union; Mexico; United States; trade agreements; climate change